2002
DOI: 10.1046/j.1432-1033.2002.02937.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ectopic anionic trypsin I in rat lungs potentiating pneumotropic virus infectivity and increased enzyme level after virus infection

Abstract: Extracellular cleavage of virus envelope fusion glycoproteins by host cellular proteases is a prerequisite for the infectivity of mammalian and nonpathogenic avian influenza viruses, and Sendai virus. In search of such target processing proteases in the airway, we recently found a new candidate trypsin‐like processing protease in rat lungs, which was induced by Sendai virus infection, and identified as ectopic rat anionic trypsin I. On SDS/PAGE under reducing and nonreducing conditions, the purified enzyme gav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…The HA 0 processing proteases reported for human IAV in animals and humans that recognize single basic motif are pancreatic trypsin (Klenk et al, 1975), plasmin from calf and chicken serum (Lazarowitz et al, 1973), blood clotting factor Xa from chick embryo (Gotoh et al, 1990), tryptase Clara from rat lungs (Kido et al, 1992), mini-plasmin from rat lungs (Murakami et al, 2001), ectopic anionic trypsin from rat lungs (Towatari et al, 2002), porcine mast cell tryptase (Chen et al, 2000), tryptase TC30 from porcine lungs (Sato et al, 2003) and transmembrane protease serine (TMPRSS) 2 and type II membrane protein human airway trypsin-like protease (HAT) (Böttcher et al, 2006) (Table 1). Why various trypsin-type HA 0 processing proteases capable of potentiating IAV infections exist in the airways?…”
Section: Ha0 Processing Proteases In the Airway For Human Seasonal Inmentioning
confidence: 99%
“…The HA 0 processing proteases reported for human IAV in animals and humans that recognize single basic motif are pancreatic trypsin (Klenk et al, 1975), plasmin from calf and chicken serum (Lazarowitz et al, 1973), blood clotting factor Xa from chick embryo (Gotoh et al, 1990), tryptase Clara from rat lungs (Kido et al, 1992), mini-plasmin from rat lungs (Murakami et al, 2001), ectopic anionic trypsin from rat lungs (Towatari et al, 2002), porcine mast cell tryptase (Chen et al, 2000), tryptase TC30 from porcine lungs (Sato et al, 2003) and transmembrane protease serine (TMPRSS) 2 and type II membrane protein human airway trypsin-like protease (HAT) (Böttcher et al, 2006) (Table 1). Why various trypsin-type HA 0 processing proteases capable of potentiating IAV infections exist in the airways?…”
Section: Ha0 Processing Proteases In the Airway For Human Seasonal Inmentioning
confidence: 99%
“…Less is known about proteases that cleave influenza viruses under conditions of natural infection. Several trypsin-like proteases isolated from rat and swine lung were shown to support replication of influenza viruses in vitro (3,9,18,25). However, it remains unclear whether these proteases play a role in in vivo infection.…”
mentioning
confidence: 99%
“…It has been suggested that soluble proteases might activate human influenza viruses in the infected host (18,19,30,43). However, analysis of cultured human respiratory epithelial cells revealed efficient HA cleavage during HA biogenesis and upon uptake of virions into target cells, suggesting that HA cleavage in the human host is a cell-associated process (47).…”
mentioning
confidence: 99%